2015
DOI: 10.1049/iet-rpg.2014.0457
|View full text |Cite
|
Sign up to set email alerts
|

Identifying wind power ramp causes from multivariate datasets: a methodological proposal and its application to reanalysis data

Abstract: Forecasting abrupt variations in wind power generation (the so-called ramps) helps achieve large scale wind power integration. One of the main issues to be confronted when addressing wind power ramp forecasting is the way in which relevant information is identified from large datasets to optimally feed forecasting models. To this end, an innovative methodology oriented to systematically relate multivariate datasets to ramp events is presented. The methodology comprises two stages: the identification of relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…To complete this section, we would like to highlight, for different reasons that will be clear later on, two recent works [32,35]. On the one hand, ref.…”
Section: Physical-based Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…To complete this section, we would like to highlight, for different reasons that will be clear later on, two recent works [32,35]. On the one hand, ref.…”
Section: Physical-based Modelsmentioning
confidence: 99%
“…On the one hand, ref. [32] is interesting because it uses data from Global Circulation Models (GCMs) (reanalysis data)to identify possible meteorological causes for WPREs and also because it applies a methodology based on wavelets and Principal Component Analysis (PCA) to estimate the best set of features (predictive variables) to estimate WPREs. On the other hand, ref.…”
Section: Physical-based Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability at longer timescales is also considered to be of greater importance to this study, as it has been found that longer-timescale, synoptic-scale weather patterns (such as cold fronts) drive variability (Kiviluoma et al, 2016). It has been noted that it is difficult to make generalisations on resource variability for a specific region based on studies done for other regions (Kiviluoma et al, 2016;Gallego-Castillo et al, 2015). This is especially true for studies considering the prevailing meteorological processes inherent to a specific region, highlighting the importance of conducting region-specific studies.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the most frequent of synoptic systems that affect South Africa's weather are extra-tropical cyclones, and the cold fronts associated with them. Little literature could be found where the underlying causative meteorological phenomena driving wind ramp events were studied (Couto et al, 2015;Gallego-castillo et al, 2015;Lacerda et al, 2017). Furthermore, attempts to find literature in which wind power ramp events associated with specific weather systems had been studied for South Africa were not successful.…”
Section: Introductionmentioning
confidence: 99%